The crude skin secretion of the pepper frog Leptodactylus labyrinthicus is rich in metallo and serine peptidases - Libério, Michelle da Silva (2014)
Peptidases are ubiquitous enzymes involved in diverse biological processes. Fragments from bioactive peptides have been found in skin secretions from frogs, and their presence suggests processing by peptidases. Thus, the aim of this work was to characterize the peptidase activity present in the skin secretion of Leptodactylus labyrinthicus. Zymography revealed the presence of three bands of gelatinase activity of approximately 60 kDa, 66 kDa, and 80 kDa, which the first two were calcium-dependent. These three bands were inhibited either by ethylenediaminetetraacetic acid (EDTA) and phenathroline; thus, they were characterized as metallopeptidases. Furthermore, the proteolytic enzymes identified were active only at pH 6.0–10.0, and their activity increased in the presence of CHAPS or NaCl. Experiments with fluorogenic substrates incubated with skin secretions identified aminopeptidase activity, with cleavage after leucine, proline, and alanine residues. This activity was directly proportional to the protein concentration, and it was inhibited in the presence of metallo and serine peptidase inhibitors. Besides, the optimal pH for substrate cleavage was determined to be 7.0–8.0. The results of the in gel activity assay showed that all substrates were hydrolyzed by a 45 kDa peptidase. Gly-Pro-AMC was also cleaved by a peptidase greater than 97 kDa. The data suggest the presence of dipeptidyl peptidases (DPPs) and metallopeptidases; however, further research is necessary. In conclusion, our work will help to elucidate the implication of these enzymatic activities in the processing of the bioactive peptides present in frog venom, expanding the knowledge of amphibian biology.